Bartonella henselae Infection: An Uncommon Mimicker of Autoimmune Disease. (17th January 2013) - Maritsi, Despoina N.; Zarganis, Diagoras; Metaxa, Zoi; Papaioannou, Georgia; Vartzelis, George
Abstract : We present a case of a seven-year-old immunocompetent female patient who developed systemic symptoms mimicking an autoimmune rather than an infectious disease. The patient presented with rash, biquotidian fever, night sweats, and arthralgias. There was no antecedent history of cat contact. Investigations showed increased inflammatory markers, leukocytosis, thrombocytosis, hypercalcemia, and raised angiotensin-converting enzyme. Interferon-gamma releasing assay for tuberculosis infection was negative. Abdominal imaging demonstrated multifocal lesions of the liver and spleen (later proved to be granulomata), chest X-ray showed enlarged hilar lymph nodes, and ophthalmology review revealed uveitis. Clinical, laboratory, and imaging features pointed towards sarcoidosis. Subsequently, raised titers (IgM 1 : 32, IgG 1 : 256) against Bartonella confirmed the diagnosis of B. henselae infection. She was treated with gentamycin followed by ciprofloxacin; repeat investigations showed complete resolution of findings. The presence of hepatic and splenic lesions in children with bartonellosis is well documented. Our case, however, exhibited certain unusual findings such as the coexistence of acute ocular and systemic involvement in an immunocompetent host. Serological testing is an inexpensive and effective way to diagnose bartonellosis in immunocompetent patients; we suggest that bartonella serology is included in the baseline tests performed on children with prolonged fever even in the absence of contact with cats in countries where bartonellosis is prevalent.